RIGHT TO THE CITY: RUANG REPRESENTASIONAL MANUSIA SILVER - Septian Rahmat Purnomo; Agung Dharma Yuda Adi Ramadhan; Tiara Yulita Sari (Jurnal Sosial Humaniora Sigli, 2023)
The silver man is not a new phenomenon. People who deliberately color their entire bodies with a layer of silver were originally a means of seeking charity. However, over time the phenomenon developed into a means of begging, and some people even consider being a silver man as a job. Silver man are often found around the traffic light area, which in the context of this research is at the intersection of Mastrip Road, Sumbersari District, Jember Regency. This research uses the perspective of Henri Lefebvre's theory of space. According to him, the creation of space will be based on the social interaction that exists in it. The purpose of this research is to find out how the sovereignty of silver man over the representational space that has been created in the city where they are one of the residents. The type of research used is qualitative with an ethnographic approach. The results showed that there was a production of a representational space due to the meeting of two spaces that had been conceptualized differently between silver man and the city government which led to the non-fulfillment of the sovereignty of the city dwellers.